Enhancing prompt perception in dementia: a comparative study of mixed reality cue modalities - Desai, Shital; Mutsuddi, Rupsha; Astell, Arlene J. (Frontiers in Sports and Active Living, 2024)
The prevalence of dementia is rapidly increasing, impacting millions worldwide and challenging individuals' ability to engage in daily activities. Active living has been identified as crucial in mitigating dementia's neurodegenerative effects, yet people with dementia often struggle to initiate and complete tasks independently. Technologies have emerged as promising solutions to provide prompts and cues for people with dementia, facilitating their engagement in activities of active living and improving their quality of life. However, ensuring these technologies maintain people’s autonomy is essential for their emotional well-being. While prompting technologies and augmentative communication strategies have shown efficacy, caregiver burden and loss of autonomy remain concerns as innovations in prompting technologies are not transferrable from research labs to people’s homes. It is anticipated that developments in sensor and wearable technologies will result in mixed reality technology becoming more accessible in everyday homes, making them more deployable. The possibility of mixed reality technologies to be programmed for different applications, and to adapt them to different behaviours and contexts, will make them more scalable. However, there is a need to develop a better understanding of modalities of prompts that are successfully and correctly perceived by people with dementia in mixed reality environments. This paper investigates interactions of people with dementia with prompts in s. Through an observation study utilizing off-the-shelf mixed reality technologies, including both Augmented Reality (AR) and Augmented Virtuality (AV) technologies, different modalities of prompts were compared for their correct and successful perception by people with dementia. We discuss the perception of various visual and audio prompts and propose guidelines for the modality of cues for people with dementia in mixed reality environments. This study lays the foundation for considering mixed reality technologies as assistive tools for people with dementia, fostering discussions on their accessibility and inclusive design in technology development.